PERENCANAAN RENCANA STRATEGIS SISTEM INFORMASI UNTUK TERCAPAINYA VISI MISI DARI RUMAH SAKIT - Febriani, Siska; Soedijono, Bambang; Arief, M. Rudyanto (Universitas Janabadra, 2019)
ABSTRACT XXX Regional General Hospital (RSUD XXX) is a Type B Hospital in Yogyakarta. XXX Hospital is the only place of reference for further treatment of patients who feel they need more sophisticated handlers. In 2016 the XXX Hospital was requested by the DIY Health Office to improve facilities and services. In following up on the request of the Yogyakarta Health Office, the RSUD XXX is currently in the process of building a building structure. However, from the increase in infrastructure built it has not been accompanied by the development of adequate technological infrastructure. From the description of the above problems, the purpose of this study is to make a strategic plan to align business objectives with the business process of the RSUD. The limitation of the problem is that in this study the researcher used the Zachman framework with matrix tables 1 to 4 (Scope, Enterprise Model, System Model, Technological Model). The final results of this study are the main activities of the XXX hospital including registration, outpatient care, hospitalization, emergency services, laboratory services, drug services, hospital services, outpatient registration and inpatient registration. Whereas for supporting activities are the procurement of logistics, tools and materials, medical workers requitment, information services. There are 7 applications that are suggested to be developed, namely the Registration application, BPJS, Poly Unit, Laboratory, E-Billing, Medical Support.Keywords: Architecture Enterprise, Informatic System, Hospital